2009
DOI: 10.3750/aip2009.39.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Cloning Two PepT1 cDNA Fragments of Common Carp, <I>Cyprinus Carpio</I> (Actinopterygii: Cypriniformes: Cyprinidae)

Abstract: Background. Common carp, Cyprinus carpio, is a model organism within Teleostei. Oligopeptides are a new and promising alternative source of amino acids in animal as well as in human nutrition. In common carp, the membrane protein that transports oligopeptides across the enterocyte membrane is encoded by the gene PepT1 (SLC15A1). The aim of this paper was to sequence the PepT1 (SLC15A1) in common carp. Materials and Methods. Intestine samples were isolated from six-week old common carp. Total RNA was isolated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several studies suggested that regulated PepT1 expression by dietary‐free amino acid, peptides and intact protein in fish could affect growth performance directly and/or indirectly (Ostaszewska et al . , ,b; Bakke et al . ; Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that regulated PepT1 expression by dietary‐free amino acid, peptides and intact protein in fish could affect growth performance directly and/or indirectly (Ostaszewska et al . , ,b; Bakke et al . ; Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…The PEPT1 gene has been characterised in many vertebrates, including fish, such as zebrafish ( Danio rerio ) ( 27 ) , sea bass ( Dicentrarchus labrax ) ( 28 ) , common carp ( Cyprinus carpio ) ( 29 ) , Atlantic salmon ( Salmo salar ) ( 30 ) , rainbow trout ( Onchorhynchus mykiss ) ( 31 ) , yellow perch ( Perca flavescens ) ( 32 ) and sea bream ( Sparus aurata ) ( 33 ) . According to these studies, the PEPT1 gene is specifically expressed in the intestinal tract and its transcript levels are related to fish nutritional status, which is down-regulated during fasting and up-regulated during refeeding ( 28 ) .…”
mentioning
confidence: 99%
“…Peptides have a faster absorption pathway in the intestine through the hydrogen/peptide symmetry in the PEPT 1, which decreases competition with other nutrients at uptake sites of enterocytes (Daniel, ). Upon entering the enterocyte, the peptides are cleaved by endogenous peptidases to form amino acids, which are then transported to the liver via the bloodstream for subsequent metabolism (Ostaszewska et al, ; Romano, Barca, Storelli, & Verri, ). The relationship between PEPT and the presence of di and tripeptides was shown for juveniles of Atlantic Cod ( G. morhua ; Bakke et al, ).…”
Section: Discussionmentioning
confidence: 99%